A study of electrode wear ratio on EDM of Ti-6AL-4V with copper-tungsten electrode - Zainal Nurezayana; Mohd Zain Azlan; Sharif Safian (MATEC Web of Conferences, 2016)
In this work, a study of electrode wear ratio (EWR) on the diesinking electrical discharge machining (EDM) of Ti-6AL-4V titanium alloy with copper-tungsten (Cu-W) electrode has been carried out. Pulse on time (ON), pulse of time (OFF), peak current (V) and servo voltage (SV) were seen as the machining parameters. The experiments were run according to the design of experiments (DOE), which is two levels of full factorial with added centre points. The experimental results reveal that pulse on time and peak current are statistically significant parameters for affecting EWR with the p-value of 0.0013 and 0.0012 respectively. Moreover, based on ANOVA, we recognized peak current as the most significant parameters which contribute 31.75%, followed by pulse on time, servo voltage and pulse on time which contribute 30.99%, 8.68% and 0.72%, respectively.